IDENTIFICATION AND QUANTIFICATION OF PINE NEEDLE ESSENTIAL OIL FROM DIFFERENT HABITATS AND SPECIES OF CHINA BY GC-MS AND GC METHOD - Yu, Jingjing; Su, Jie; Li, Fenghua; Gao, Jianli; Li, Bo; Pang, Minxia; Lv, Guiyuan; Chen, Suhong (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Fresh pine needles, which evergreen, renewable and can be collected at any time, have abundantessential oil. The pine needle essential oil possess various biological activities, including antimicrobial, antioxidant,anti-inflammatory, cardioprotective properties etc., and can be widely used as medicine or medical raw materials,fragrances etc. So in order to make full use of pine needle plant resources, especially essential oil, the identification andquantification of essential oil were investigated.Materials and Methods: GC-MS was used to identified compounds in pine needle essential oil of Pinus massonianaLamb. from Zhejiang, and GC method was developed for determining 5 compounds (namely α-pinene, β-pinene,limonene, bornyl acetate, β-caryophyllene) in pine needle essential oil from different habitats of Pinus massonianaLamb. and different species (Pinus koraiensis Sieb. et Zucc., Pinus sylvestris var. mongolica Litv., Abies holophyllaMaxim.). Hierarchical clustering analysis (HCA) was used to evaluate homogeneity of pine needles in China.Results: 42 compounds(monoterpenes and sesquiterpenes) were identified by GC-MS, which accounted for 99.62% oftotal essential oil, particularly contained α-and β-pinene (45.23%). Quantification results showed content of bornylacetate were the lowest, while content of α-pinene, β-pinene were all high except Sichuan, among them α-pinene werehigher than β-pinene except for Shandong and Jiangsu, and total content of essential oil in Guangxi is the highest,Jiangsu was the lowest within Pinus massoniana from different habitats. Within pine needle from different species, thehighest total content was Pinus koraiensis, the lowest was Pinus sylvestris, Interestingly, the highest content of bornylacetate was Abies holophylla. By HCA, samples were sorted into two clusters, Abies holophylla and the other, that isAbies holophylla is different from Pinus massoniana, Pinus koraiensis and Pinus sylvestris. Pinus massoniana fromSichuan is different from other Pinus, in which limonene was the highest in all samples.Conclusions: Compounds of pine needle essential oil vary greatly between genus, while smaller between species, socomposition differences among pine needle essential oil was related with genus and species. Abies holophylla isdifferent from other pinus species, and Pinus massoniana from Sichuan is different from other habitats. Pine needleessential oil contains abundant α-and β-pinene, which can be used as an alternative raw materials source of pinene. AndAbies holophylla and Pinus massoniana from Sichuan can become bornyl acetate and limonene alternative source ofraw materials.